Improves The Ability To Calculate Children Through The Constructive Game : How Improves The Ability To Calculate Children Through The Constructive Game - Reflina Sinaga; Ester Julinda Simarmata (International Interdisciplinary Conference on Sustainable Development Goals, 2020)
The research objective of this paper is to determine the increase in children's numeracy skills through constructive play in grade 1 students in elementary schools. Elementary school is basic education that is organized with the aim of facilitating the growth and development of children as a whole or emphasizing the development of all aspects of the child's personality as it means that elementary school education provides opportunities to develop children's personalities, therefore education for early childhood especial in schools. The research method is the method used by researchers in collecting research data. The method used in this research is classroom action research. Based on the results of research and discussion, it can be concluded that the ability counting the child at by using constructivist games has been successful with the number of students 19 people, with a category of 10 boys and 9 girls can be increased through the use of constructive play media. This study shows that there is an increase in numeracy skills by using constructive games for students of SD Aghia Sophia Medan. The findings of this study also provide evidence that using constructive games requires students to be active in learning, this is because students themselves are looking for the material to be studied, students also feel happy and challenged in learning because constructive games are applied by learning while playing.